Effect of statins and antihyperglycemics on chronic kidney disease in patients with type 2 diabetes mellitus: a retrospective cohort study with a 12-year follow-up - Ammar Abdulrahman Jairoun; Chong Chee Ping; Baharudin Ibrahim; Dina Farhan Al Jawamis; Asma Khaled Al Jaberi; Tasnim Dawoud; Khuloud Jamal Mohammed; Faris El-Dahiyat; Moyad Shahwan (Journal of Pharmaceutical Policy and Practice)
Background: Chronic Kidney Disease (CKD) represents a significant worldwide health challenge, with far-reaching implications for both patients and healthcare systems. This study aimed to identify the incidence of CKD at stages 3–5, analyzed the impact of statin and other antihyperglycemic interventions, on the CKD progression in individuals with T2DM.Methods: This was a single-center retrospective cohort study based on data derived from electronic medical records (EMR) of UAE populations with diabetes mellitus, registered at outpatient clinics at Tawam Hospital in Al Ain, UAE, between January 2011 and December 2021. T2DM patients aged ≥ 18 years who had serum HbA1c level ≥ 6.5% and using one of the statin therapies were inclusion criteria. Patients with T1DM, who had undergone permanent renal replacement therapy, with under 1 year of follow-up and missing or incomplete data were excluded from the study. The collected data encompassed socio-demographics, detailed medical history, anthropometric measurements, laboratory analyses, clinical parameters, disease characteristics, and medications.Results: Our study included a cohort of 1,003 individuals. We observed 388 subjects developed CKD stages 3–5 across an average monitoring duration of 11.7 years. This resulted in a cumulative incidence of 38.7%, translating to an incidence rate of 38 cases per 1000 person-years. There was a statistically significant difference in the cumulative incidence of CKD stages 3 ± 5 according to statin therapy (P = 0.047). High intensity statin users are more likely to develop a CKD stage 3–5 compared to low/moderate intensity users and to no statin users respectively (44.3% vs 37.9%), (44.3% vs 30.9%). Conversely, the use of Biguanides was associated with a decreased probability of CKD progression (37.9% vs. 52.8%; P = 0.001), whereas Insulin users demonstrated a heightened risk (54.2% vs. 34.1%; P < 0.001).Conclusion: The findings emphasise the pivotal role of personalised treatment strategies, particularly concerning statin therapy and other medications, in populations at high risk.